2012
DOI: 10.3109/09546634.2012.683767
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of infliximab in hidradenitis suppurativa

Abstract: Long-term IFX therapy might be an efficient, well-tolerated, safe option for patients with short-time evolution, severe HS. Relapse is common after 8 months of continuous treatment, especially in patients with more severe disease and in those treated with IFX in monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
0
31
0
1
Order By: Relevance
“…Even though an improvement is often reported in the inflammatory lesions during infliximab therapy, recurrence is also high during therapy. Up to 50 % develop new lesions after a treatment period of 37 weeks [69][70][71]. Moriatry et al [71] suggested that an 8-week interval is too long for HS patients and that a 4-week interval is more effective [71], because most patients report a gradual increase in inflammatory lesions around 6 weeks after infusion.…”
Section: Infliximabmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though an improvement is often reported in the inflammatory lesions during infliximab therapy, recurrence is also high during therapy. Up to 50 % develop new lesions after a treatment period of 37 weeks [69][70][71]. Moriatry et al [71] suggested that an 8-week interval is too long for HS patients and that a 4-week interval is more effective [71], because most patients report a gradual increase in inflammatory lesions around 6 weeks after infusion.…”
Section: Infliximabmentioning
confidence: 99%
“…It binds to the soluble and transmembrane forms of TNF-a, inhibiting TNF-a from binding to its receptors [68]. Multiple studies have reported on the efficacy of infliximab in patients with HS [69][70][71]. Mostly the same dose is given as in psoriasis, with 5 mg/kg infliximab at weeks 0, 2, and 6, and continued every 8 weeks thereafter [3,72].…”
Section: Infliximabmentioning
confidence: 99%
“…As regards infliximab, even if the first RCT phase II crossover study on 38 patients (15 treated and 28 placebo) was published in 2010 [25,] no additional phase III RCT studies have been published. A cumulative response rate of 58% (improvement ≥50% in 42 patients) has been reported in case reports with 73 patients with moderate to severe HS [107,108,109,110,111,112,113,114,115,116]. Infliximab is administered intravenously over a period of 2 h, whereas adalimumab is administered subcutaneously.…”
Section: Treatmentmentioning
confidence: 99%
“…As a prominent side effect, we found in the literature a case of bilateral Candida chorioretinitis in a patient with HS treated with etanercept [30]. The efficacy of infliximab in HS is consistently reported, as shown in table 4, often coinciding with Crohn's disease (cases summarized in table 4) [31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60]. In these last cases, it has been postulated that the improvement could be due to the similarity between the two diseases.…”
Section: Review and Discussionmentioning
confidence: 93%